2010
DOI: 10.1245/s10434-009-0895-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic Role of Podoplanin in Esophageal Squamous-Cell Carcinoma

Abstract: There is a role for podoplanin in tumorigenesis and malignant progression in ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
69
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 29 publications
10
69
3
Order By: Relevance
“…The current findings are in agreement with those obtained by Nakayama et al (18), Rahadiani et al (23) and Tong et al (22), which demonstrated a significant correlation between PDPN tumor expression and pathological stage, depth of tumor invasion and lymph node metastasis in esophageal carcinoma.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The current findings are in agreement with those obtained by Nakayama et al (18), Rahadiani et al (23) and Tong et al (22), which demonstrated a significant correlation between PDPN tumor expression and pathological stage, depth of tumor invasion and lymph node metastasis in esophageal carcinoma.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in accordance with the results of studies by Kimura et al (19) and Okazawa et al (20), and our previous study (8), which used immunohistochemistry to demonstrate that esophageal tumors express VEGF-C and VEGF-D. In addition, Tanaka et al (21) used RT-qPCR to demonstrate that esophageal cancer cells express VEGF-C, and Tong et al (22) and Rahadiani et al (23) identified PDPN overexpression in esophageal carcinoma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Podoplanin knockout mice have lymphatic defects associated with diminished lymphatic transport, congenital lymphedema and dilation of lymphatic vessels [29], suggesting that, under physiological conditions, podoplanin plays an important role in regulating peripheral lung cell proliferation and lymphatic vascular development. Apart from head and neck squamous cell carcinoma, particularly in oral cancer [23,30], podoplanin is expressed in carcinoma of the skin [31], lung [32], uterus [33], colon [34], oesophagus [35,36], in mesothelioma [37] in astrocytoma [38,39]. Investigations have shown that podoplanin, the oncofetal protein M2A recognised by the D2-40 antibody and the type I alveolar cell marker hT1ά-2 are identical proteins [25].…”
Section: Introductionmentioning
confidence: 99%
“…Podoplanin known as D2-40 is a mucin-type transmembrane glycoprotein and a specific marker for lymphatic endothelium. Podoplanin is a candidate CSC marker for human squamous cell carcinoma because the knockdown of podoplanin expression results in vulnerability to anticancer drugs, defective invasion and tumorigenic activity (8)(9)(10). It has been reported that a high level of podoplanin expression correlates with a poor prognosis in oral and esophageal cancer (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%